2016
DOI: 10.1016/j.bpj.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation within the First 17 Residues of Huntingtin Exon 1 Alters Aggregation and Lipid Binding

Abstract: Huntington's disease (HD) is a genetic neurodegenerative disorder caused by an expanded polyglutamine (polyQ) domain near the N-terminus of the huntingtin (htt) protein. Expanded polyQ leads to htt aggregation. The first 17 amino acids (Nt(17)) in htt comprise a lipid-binding domain that undergoes a number of posttranslational modifications that can modulate htt toxicity and subcellular localization. As there are three lysines within Nt(17), we evaluated the impact of lysine acetylation on htt aggregation in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 115 publications
(217 reference statements)
5
90
0
1
Order By: Relevance
“…246 Proteomic mapping by MS demonstrated that K9 is substantially acetylated in mammalian cell lysates, 233 and this residue is preferentially chemically acetylated in vitro. 247 Interestingly, acetylation of N17 reduces aggregation into fibrils while promoting the formation of large oligomeric species. 247 Acetylation of N17 also decreases htt’s affinity for lipid membranes, and computational studies suggested that K9 may play a key role in the initial binding of N17 to lipids.…”
Section: Post-translational Modifications Impact Aggregation and Toximentioning
confidence: 99%
See 1 more Smart Citation
“…246 Proteomic mapping by MS demonstrated that K9 is substantially acetylated in mammalian cell lysates, 233 and this residue is preferentially chemically acetylated in vitro. 247 Interestingly, acetylation of N17 reduces aggregation into fibrils while promoting the formation of large oligomeric species. 247 Acetylation of N17 also decreases htt’s affinity for lipid membranes, and computational studies suggested that K9 may play a key role in the initial binding of N17 to lipids.…”
Section: Post-translational Modifications Impact Aggregation and Toximentioning
confidence: 99%
“…247 Acetylation of N17 also decreases htt’s affinity for lipid membranes, and computational studies suggested that K9 may play a key role in the initial binding of N17 to lipids. 247 …”
Section: Post-translational Modifications Impact Aggregation and Toximentioning
confidence: 99%
“…[11] Chaibva et al reported that acetylation of Httex1 retards fibrils formation in vitro. [9] However, it is noteworthy that their findings were based on nonselective chemical acetylation of all lysine residues in a model peptide of Httex1 lacking the last 39 C-terminal residues and containing two non-native lysines residues which were also partially acetylated. To investigate the effect of lysine acetylation on Httex1 aggregation, we produced both WT (23Q) and mutant (43Q) Httex1 acetylated at single lysine residues (AcK6, AcK9, and AcK15).…”
Section: Main Textmentioning
confidence: 99%
“…Although acetylation of lysine residues within Nt17 has been proposed to play a role in regulating its association with membranes, [9] only K9 was reported to be acetylated in HEK cells [10] and was proposed to play an important role in Htt clearance. [11] Chaibva et al reported that acetylation of Httex1 retards fibrils formation in vitro.…”
Section: Main Textmentioning
confidence: 99%
“…The enhanced toxicity of mHTT lacking its N17 domain may be due to the fact that this domain modulates HTT's interaction with multiple chaperone proteins that affect the size, density, and location of HTT aggregates through acetylation, ubiquitination, and sumoylation of this domain [118,120,121].…”
Section: Wild Type Huntington Functionsmentioning
confidence: 99%